Tatak Pilipino [Episode no. 27]. ([Quezon City ABS-CBN, 1991)
A unique display of Pilipino ways and style.
4 Significant Filipinos in movie industry, Lamberto Avellana (15 min.) -- Teroy De Guzman (10 min.) -- Canupin (10 min.) -- Lino Brocka (25 min.)
In English and Pilipino.
Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Avellana, Lamberto; Brocka, Lino; De Guzman, Teroy; Filipinos -- Biography; Canuplin